Numerical modelling of bolted composite joints. Bolts rigidity effect on normal stresses in the composite layers - Y. Dyfuchyn; K. Rudakov (Mechanics and Advanced Technologies, 2017)
Modern finite element programs have the opportunity to create finite element models (FEM) by "gluing" uncoordinated meshes of finite elements. This allows, in particular, to obtain relatively small 3D models of polymeric composite materials (PCM) in bolted connections for PC calculations, in which the PCM in the hole zones is modeled layer by layer, and at some distance from them - approximately, according to the theory of the "effective module". In previous model calculations of single-shear two-row bolted connection with PCM (contact task) with detailed layer-by-layer modeling of the PCM structure in the hole zones, regularities were revealed for the distribution of contact forces in the bolt-hole surface contact, bolt stresses and near- contacting in the holes with the lateral surfaces of the bolts. In the article, based on numerical calculations, the regularities of changes in normal stresses on the contact surfaces of holes in PCM, in laying layers at 0 and 90 degrees, were found, depending on the rigidity of the bolts.